Design and analysis of an object-oriented discrete-event simulation engine for ATM telecommunication networks. (6th October 2008) - Cortes, P.; Munuzuri, J.; Onieva, L.; Carazo, J.M.
Asynchronous Transfer Mode is a cell-oriented transfer mode based on asynchronous time division multiplexing. ATM manages different types of services with different requirements using cell structures and virtual channels and paths. Most of the proposals in terms of routeing algorithms, cell-scheduling function or control of traffic are formulated and analysed separately and need to be tested in prototypes or simulation scenarios. This paper presents an object-oriented discrete-event simulation engine for ATM networks. The simulation tool is tested in different scenarios for voice and data traffic, which correspond up to 95% of the total traffic in real-life telecommunication networks.